SISTEM PENDUKUNG KEPUTUSAN PENGELOLAAN PERIKANAN (LAUT) PADA DINAS KELAUTAN DAN PERIKANAN KOTA SEMARANG BERBASIS WEB (Information Technology and Telematics, 2013)
Analysis of the new planning system in fisheries management decision support system at the Department of Marine and Fisheries Semarang includes an evaluation of the proposed system, Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD), database specifications, process design and implementation plan. Based on the analysis and research on the author, it can be concluded that the decision-making process was made with modeling that takes into account the various factors that serve as models of assessment. Decision-making process based on the assessment of coastal condition that the object of this PPI (fish landing port) and TPI (Fish Auction). Assessment parameters include fish production data, the data infrastructure supporting facilities of fishing activities. From these data, it can be done for the feasibility assessment process decisions will be made by the system which is then used as a support for decision by the Head of Department.Keywords: Decision Support System, Fisheries Management, Fish Landing Port, Place Fish Auction, PHP, MySQL, Capture fisheries.  1